A Comparison of Cognate Dialect Features in Javanese, Sundanese, Cirebon, and Indramayu - Wibowo, Ridha Mashudi (Sutasoma : Jurnal Sastra Jawa, 2025)
This study aims to identify cognates based on form and meaning among Javanese, Sundanese, Cirebon, and Indramayu vocabularies and analyze their dialectal relationships. Using a list of one hundred Swadesh vocabulary items sourced from dictionaries of the four languages, the data were phonetically transcribed and compared to identify shared lexemes. Dialectometric analysis was then applied to quantify lexical distances and classify dialectal relationships. The findings show that the four languages share 28 cognates and exhibit varying degrees of linguistic proximity: Javanese and Cirebon show the closest relationship, while other pairs are classified as distinct dialects. While the study integrates qualitative and quantitative approaches and contributes insights into less-studied dialects such as Cirebon and Indramayu, it is limited by its reliance on secondary data and lack of fieldwork. Future research should incorporate direct elicitation from native speakers, phonological correspondence analysis, the etymological distinction between cognates and loanwords, and sociolinguistic and geographical mapping to deepen the understanding of dialectal variation in Java